(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
New data on some critical taxa of Pinophyta in Ukrainian flora are given and discussed with presenting identification keys. Next taxa are treated: Ephedra arborea Lag. – as synonym of E. distachya L., Pinus pallasiana Lamb. – as P. nigra J. F. Arnold subsp. pallasiana (Lamb.), P. pityusa Steven var. stankewiczii Sukacz. – as P. brutia Ten. var. pityusa (Steven) Silba.; P. sylvestris L. – as divided into three varieties: var. sylvestris, var. cretacea Kalen. ex Kom. and var. hamata Steven; P. mugо Turra – as divided into two subspecies: subsp. mugo and subsp. rotundata (Link) Janen. et H. Neumayer; Larix decidua Mill. – as divided into two varieties: var. decidua and var. polonica (Racib. ex Wóycicki) Ostenf. et Syrach; Juniperus oxycedrus L. replaced by J. deltoides R.P. Adams, J. communis L. – as divided into two varieties: var. communis and var. saxatilis Pall.; Platycladus orientalis (L.) Franco is given as naturalized in Ukraine for the first time.